KARAKTERISTIK MORFOLOGI POLEN (Calamus acehensis) - Asra, Revis; Wahyuni, Silvia; Adriadi, Ade; Febrianti, Arikah (PendIPA Journal of Science Education, 2025)
Calamus acehensis (Rustiami), known as Aceh jernang rattan, is an endemic plant with high economic value in Aceh Province. This jernang produces red resin from its fruit which is used as a natural dye for rattan handicrafts as well as in traditional medicine, such as wound medicine, headaches, and post-natal pilis. The advantage of C. acehensis over other jernang species lies in its rapid growth and high resin production at a young age. At the age of two years, the plant has reached a height of two meters and started to bear fruit. Distinctive morphological features include stem internodes up to 50 cm, leaves up to 2 meters long, petioles 35 cm long, and black leaf sheaths with long and dense spines. This study aims to assess pollen morphology to determine its pollination system and taxonomic status. Pollen samples were taken from C. acehensis growing in Rieseh Tengoh Village, Aceh and from cultivation in Jambi. Analysis was conducted using a Scanning Electron Microscope (SEM) at the UGM Integrated Research and Testing Laboratory. Results showed that both samples had small pollen size, 1.212 µm (Aceh) and 1.116 µm (Jambi), with a single monocolpate aperture shape and flat exine ornamentation. These characteristics indicate the potential for wind-assisted cross-pollination (xenogamy) (anemogamy), providing important insights for the conservation and cultivation of Acehnese jernang.